THERMAL EFFECT OF COCONUT CREAMS ABILITY TO ADSORB CALCIUM(II) - Fatmawati Tahir; Ani Setyopratiwi; Sri Sudiono (Universitas Gadjah Mada, 2002)
Study of thermal effect of coconut cream's ability to adsorb Ca (II) has been done at various temperatures of 49 oC, 59 oC and 80 oC. The adsorption study was performed to check capacity, energy and rate of adsorption by varying the number of initial concentration of CaCl2 bounded on coconut protein. This research was also done to determine number of Ca (II) in the coconut protein using the salt addition and elicits reaction methods. The result showed that adsorption ability tends to increased with the increase of temperature). Coconut cream heated at 59 oC adsorb Ca(II) with the highest adsorption capacity of 3.98 mg/g and K = 3.48x104 mol-1. The salt addition method on the coconut cream gives more Ca (II) than elicit reaction method. The first method gives 0.01137 mol/L and the second was 0.02845 mol/L. Based on the energy of adsorption, cream without heating had 20.59 kJ/mol as a physical adsorption and heating effect at temperatures 49 oC, 59 oC and 80 oC had 24.95; 28.87 and 24.87 kJ/mol respectively as a chemical adsoprtion with the rate of adsorptions of 0,0054; 0,0510 dan 0,3. 10-4 minute-1, respectively.